2018
DOI: 10.1002/cam4.1840
|View full text |Cite
|
Sign up to set email alerts
|

Expression of CD81 and CD117 in plasma cell myeloma and the relationship to prognosis

Abstract: In this study, the immunophenotype was retrospectively analyzed in 131 patients who received initial treatment for plasma cell myeloma (PCM) and the relationships of CD81 and CD117 with the clinicopathologic characteristics and prognosis were further evaluated. The Kaplan and Meier method and Cox regression survival analysis model were used to determine whether CD117 and CD81 were factors affecting the overall survival (OS) and progression‐free survival (PFS) of PCM patients. CD117 and CD81 positivity was demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 24 publications
(36 reference statements)
6
29
0
Order By: Relevance
“…In breast cancer, CD81 was also revealed to be upregulated in tumor tissues, associated with poor overall survival, and promoted tumor cell proliferation and migration (13). In plasma cell myeloma, it was revealed that CD81 was an independent factor affecting the overall survival and progression-free survival of patients, and CD81 positivity predicted poor prognosis (29). The aforementioned studies demonstrated that CD81 also has prognostic value in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In breast cancer, CD81 was also revealed to be upregulated in tumor tissues, associated with poor overall survival, and promoted tumor cell proliferation and migration (13). In plasma cell myeloma, it was revealed that CD81 was an independent factor affecting the overall survival and progression-free survival of patients, and CD81 positivity predicted poor prognosis (29). The aforementioned studies demonstrated that CD81 also has prognostic value in cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting SYK has shown promising therapeutic effects in B cell malignancies, including chronic lymphoid leukemia (D. Liu & Mamorska‐Dyga, ), and in MM, inhibition of SYK resulted in significant decreases in cell survival and migration (Lorenz et al, ). Previous studies have demonstrated that CD81 is an independent prognostic factor in MM and may be associated with MM pathogenesis (Arana et al, ; F. Chen et al, ; Paiva et al, ). Expression of CD9 in MM cells is related to the disease status and survival of patients with MM, and CD9 was found to be involved in transendothelial invasion in an MM mouse model (De Bruyne et al, ).…”
Section: Discussionmentioning
confidence: 97%
“…Cell function test results showed that circ_0069767 played a role of tumor suppressor gene in MM, explained why the higher circ_0069767 expression linked to better PFS and OS. Our previous studies showed that patients with high expression of C-KIT protein (CD117) had better PFS and OS, 21 and circ_0069767 was derived from the C-KIT gene, which may further explain why patients with positive CD117 have improved PFS and OS. Some research showed that circRNA was produced by co-transcription and competed with conventional splicing during the production process.…”
Section: Discussionmentioning
confidence: 98%
“…In our previous studies, MM patients with high C-KIT (CD117) expression were observed of better prognosis compared with patients with low C-KIT (CD117) expression. 21 According to the circBase database, there are 12 circular RNAs derived from the C-KIT gene, and circ_0069767 was found in the K562 cells, which belong to the same blood tumor as multiple myeloma. So I tried qRT-PCR detection of circ_0069767 first, and the preexperiment results showed that there was a difference in expression of MM compared with the normal control group.…”
Section: Introductionmentioning
confidence: 99%